The impact of obesity on economy - Maevska, Catalina (My University, 2014)
In our days food plays an important role for every person (it is a source of energy), but not everybody can eat healthy. That is why this topic is so acute now. Don’t think that global economy and unhealthy food are far away from each other. They are closely connected and obesity has a large influence on the economy.
Keywords: obesity; economy; ожиріння; економіка; ожирение; экономика; food; еда; їжа